Christian Spirituality and Transpersonal Sociology - Moberg, David O. (Research in the social scientific study of religion, 2002)
The realities that undergird transpersonal sociology are as old as human existence and are clearly reflected in the Judea-Christian Scriptures, beginning with God's creation of male and female humanity in his own image. Although the essence of that "image" is spirit, the social sciences have neglected spirituality until recently. Spirituality is a major theme of the Bible, which provides rich data to stimulate the development of transpersonal sociology. Differences between actual and alleged teachings of the Bible and variations among various types of Christians influence research on religion and spirituality. The universality of religion in all human cultures reflects an innate search for meaning that makes comparative research on religion and spiritualities existentially and theoretically important. The development of transpersonal sociology will contribute significantly to the applied, theoretical, and methodological aspects of the sociology of religion and spirituality as well as to sociology as a whole.